Analisis Penentu Perbezaan Upah Mengikut Kemahiran di Malaysia - Wail, Nik Azma; Ismail, Rahmah; Yussof, Ishak (Sains Humanika, 2011)
In Malaysia, demand for skills has been changing dramatically as a result of economic transformation. This subsequently resulted in changes in wage ratio between skills, which is more favourable towards skilled workers. However, it has been argued that wage rate does not merely depend on the demand for labour, but there are other factors that can influence workers’ wages. These include human capital variables like educational attainment, experience and training; demographic factors and job sectors. Even after taking into account the variations in these productivity-related variables, occupational wage differentials may still prevail as a result of employers’ discriminatory practice. This paper attempts to measure wage differentials determinants by skills in Malaysia. The analysis is based on 2,216 heads of households data collected in 2007/2008. The result revealed that human capital variables play a major role in determining the level of wage and its differentials between skills. Moreover, the result demonstrates that 64.25 percent of skilled-semi skilled wage differentials are explained by the incorporated variables in the wage model, whereas 35.75 percent are unexplained. This unexplained portion includes the employers’ discriminatory practice against their workers. For the skilled-unskilled wage differentials 77.2 percent are explained and 22.8 percent are unexplained.